The root pathogen Aphanomyces euteiches secretes modular proteases in pea apoplast during host infection - Kiselev, Andrei; Camborde, Laurent; Carballo, Laura Ossorio; Kaschani, Farnusch; Kaiser, Markus; van der Hoorn, Renier A. L.; Gaulin, Elodie (Frontiers in Plant Science, 2023)
To successfully colonize the host, phytopathogens have developed a large repertoire of components to both combat the host plant defense mechanisms and to survive in adverse environmental conditions. Microbial proteases are predicted to be crucial components of these systems. In the present work, we aimed to identify active secreted proteases from the oomycete Aphanomyces euteiches, which causes root rot diseases on legumes. Genome mining and expression analysis highlighted an overrepresentation of microbial tandemly repeated proteases, which are upregulated during host infection. Activity Based Protein Profiling and mass spectrometry (ABPP-MS) on apoplastic fluids isolated from pea roots infected by the pathogen led to the identification of 35 active extracellular microbial proteases, which represents around 30% of the genes expressed encoding serine and cysteine proteases during infection. Notably, eight of the detected active secreted proteases carry an additional C-terminal domain. This study reveals novel active modular extracellular eukaryotic proteases as potential pathogenicity factors in Aphanomyces genus.